ANALYSIS OF SPATIAL RELATIONSHIP BETWEEN GROUNDWATER POTENTIAL ZONES AND BOREHOLE YIELDS IN OKENE LOCAL GOVERNMENT AREA, KOGI STATE, NIGERIA - Adaviruku, P. E.; Akpu, B.; Zubairu, S. M.; Oyatayo, K. T. (FUDMA JOURNAL OF SCIENCES, 2023)
The quantity of water that can be extracted from a borehole is directly related to the groundwater potential of an area among other things. Boreholes drilled in areas of low groundwater potential have every tendency to fail. There have been reported cases of borehole failures in Okene Local Government Area of Kogi state. This study therefore aimed at analyzing the potentiality of groundwater and the spatial relationship between borehole yield and groundwater potential zones in the area. Various data which include Sentinel 2 satellite image, Digital Elevation Model, geological map, rainfall data and borehole yield data were analyzed to produce various zones of groundwater potential, and validated using existing borehole yields and the relationship was tested using Pearson correlation. The result of this study reveals that the low potential zone covers 33.2%; moderate potential zone occupies 44.9% which cuts across the whole of Okene LGA and the high potential zone covers 21.9% mainly found around the western part of the area. The Pearson moment correlation analysis result revealed a strong positive correlation (R) value of 0.919. The correlation value shows that there is a strong positive relationship between the existing borehole yields in the study area and the groundwater potentiality map produced from the analysis. The study concluded that there is a strong positive relationship between the existing borehole yields and the groundwater potential zones in Okene Local Government Area.